Enhancing the Performance of Tangential Flow Microfiltration for Bioreactor Clarification - Amir Hossein Mostafavi; Liang-Kai Chu; Xianghong Qian; John Paul Smelko; Da Zhang; Andrew Zydney; Sumith Ranil Wickramasinghe (Membranes)
Tangential flow microfiltration is easily adapted for batch and continuous bioreactor clarification. The permeate can be introduced directly to the subsequent capture step. However, the commercial use of tangential flow filtration (TFF) is limited by membrane fouling, leading to a compromised performance. Here, we explored the possibility of reducing membrane fouling by integrating a hydrocyclone as the primary clarification operation. The overflow from the hydrocyclone was introduced directly as the feed to the microfiltration module. Chinese hamster ovary cells were used as the feed stream to investigate the feasibility of this integrated process. A range of cell viabilities from 0% (cell lysate) to 96% were investigated. The cell densities ranged from 0.9 to 10 million cells per mL. Two commercially available hollow fiber microfiltration membranes were used, an essentially symmetric membrane and a reverse asymmetric membrane where the more open support structure faced the feed stream. The reverse asymmetric membrane was more resistant to fouling in the absence of an integrated hydrocyclone. Integrating a hydrocyclone led to a reduction in the flux decline for the symmetric membrane, but did not affect the performance of the reverse asymmetric membrane. The careful choice of membrane morphology and pore size is important when designing an integrated process.